2018
DOI: 10.22610/jebs.v10i1.2095
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Buying Behavior at Shopping Malls: Does Gender Matter?

Abstract: The development of shopping malls is a major social and global phenomenon that has unearthed a novel facet for customer satisfaction and their consequent or relative buying behavior. The aim of his paper was to explore the gender differences in consumer buying behavior at selected Durban shopping malls. It is an observational cross-sectional study carried out on 700 randomly selected respondents to study buying capacity, buying behavior and shopping experience of male and female consumers at shopping malls in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…The differences between male and female shoppers' behaviors could be affected by service excellence, efficiency, convenience and so forth (Ameen et al, 2020). There are significant gender differences in the average time spent in shopping; female shoppers usually shop for a longer time and carefully consider offers and resources available (Katrodia and Soni, 2018). Therefore, this study aimed to understand gender differences among consumers in shopping behavior and preferences, which may offer unique management for the retailers and brands.…”
Section: Moderating Effect Of Gendermentioning
confidence: 99%
“…The differences between male and female shoppers' behaviors could be affected by service excellence, efficiency, convenience and so forth (Ameen et al, 2020). There are significant gender differences in the average time spent in shopping; female shoppers usually shop for a longer time and carefully consider offers and resources available (Katrodia and Soni, 2018). Therefore, this study aimed to understand gender differences among consumers in shopping behavior and preferences, which may offer unique management for the retailers and brands.…”
Section: Moderating Effect Of Gendermentioning
confidence: 99%
“…Some scholars (Deshwal, 2016; Pinto et al , 2020) have suggested that the extent of consumerism varies from person to person based on their demographic profile. Pinto et al (2020) found that females are highly influenced towards PED, whereas males are not much influenced because of different habits and perceptions (Katrodia et al , 2018) . Abdullah (2017) found that consumers with less education and between 18 and 38 of age found that PED is more effective than other groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, Lucia-Palacios et al (2018) found that gender differences in shopping experience in shopping malls only exist among more frequent shoppers and among negative low-arousal shoppers. Katrodia and Soni (2018) found that there are significant gender differences in average time spend in shopping in shopping malls.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Over the years, shopping malls have made a considerable influence on the economic and social welfare of both consumers and communities (Haj-Salem et al, 2016;Katrodia and Soni, 2018).…”
Section: Introductionmentioning
confidence: 99%